Sagacious confucius’ pillow elixir ameliorates Dgalactose induced cognitive injury in mice via estrogenic effects and synaptic plasticity - Zhao, De-Ping; Lei, Xia; Wang, Yue-Ying; Xue, Ao; Zhao, Chen-Yu; Xu, Yan-Ming; Zhang, Yue; Liu, Guo-Liang; Geng, Fang; Xu, Hong-Dan; Zhang, Ning (Frontiers in Pharmacology, 2022)
Alzheimer's disease (AD) is a growing concern in modern society, and there is currently a lack of effective therapeutic drugs. Sagacious Confucius' Pillow Elixir (SCPE) has been studied for the treatment of neurodegenerative diseases such as AD. This study aimed to reveal the key components and mechanisms of SCPE's anti-AD effect by combining Ultra-high Performance Liquid Chromatography-electrostatic field Orbitrap combined high-resolution Mass Spectrometry (UPLC-LTQ/Orbitrap-MS) with a network pharmacology approach. And the mechanism was verified by in vivo experiments. Based on UPLC-LTQ/Orbitrap-MS technique identified 9 blood components from rat serum containing SCPE, corresponding to 113 anti-AD targets, and 15 of the 113 targets had high connectivity. KEGG pathway enrichment analysis showed that estrogen signaling pathway and synaptic signaling pathway were the most significantly enriched pathways in SCPE anti-AD, which has been proved by in vivo experiments. SCPE can exert estrogenic effects in the brain by increasing the amount of estrogen in the brain and the expression of ERα receptors. SCPE can enhance the synaptic structure plasticity by promoting the release of brain-derived neurotrophic factor (BDNF) secretion and improving actin polymerization and coordinates cofilin activity. In addition, SCPE also enhances synaptic functional plasticity by increasing the density of postsynaptic densified 95 (PSD95) proteins and the expression of functional receptor AMPA. SCPE is effective for treatment of AD and the mechanism is related to increasing estrogenic effects and improving synaptic plasticity. Our study revealed the synergistic effect of SCPE at the system level and showed that SCPE exhibits anti-AD effects in a multi-component, multi-target and multi-pathway manner. All these provide experimental support for the clinical application and drug development of SCPE in the prevention and treatment of AD.